Eicosapentaenoic acid supplementation alleviates pruritus, enhances skin moisture, and mitigates depression in maintenance hemodialysis patients - Lin, Ya-ling; Wang, Chia-Liang; Chiang, Tsay-I (Frontiers in Nephrology, 2024)
BackgroundThe objective of this study is to investigate the effects of oral supplementation with eicosapentaenoic acid (EPA) on circulating inflammatory factors, cardiometabolic parameters, skin moisturization, and the consequent symptoms of pruritus and depression in maintenance hemodialysis patients.Materials and methodsA total of 60 maintenance hemodialysis patients with severe pruritus symptoms completed this randomized, placebo-controlled study. Subjects of treatment group (n = 30) were instructed to consume 1000 mg fish oil (>900 mg EPA) and subjects of placebo group (n = 30) were instructed to consume 1000 mg soybean oil twice daily for 3 months. 5-D pruritus scoring, the Beck Depression Inventory (BDI) scale, skin moisture, serum creatinine, inflammatory factors, and cardiometabolic parameters were examined at baseline, and at the first, second, and third month post-supplementation.ResultsA significantly decreased pruritus level was observed in the treatment group, whereas an opposite result was observed in the placebo group. Increased skin moisture levels on both the face and arms were observed in the treatment group, but not in the placebo group. Supplementation of EPA significantly decreased serum CRP and IL-6 levels. Significant decreases in total cholesterol (CHO), and triglycerides (TG) levels were observed; however, a decrease in high-density lipoprotein (HDL) level was observed in the treatment group. There was no change in plasma creatinine (CR) observed in both groups. A significantly decreased BDI score was observed, whereas the opposite result was observed in the placebo group. A correlational study showed that the severity of pruritus was significantly associated with skin moisture and serum CRP. The severity of pruritus was also positively correlated with the BDI score.ConclusionSupplementation of EPA may provide multiple benefits including alleviating pruritus symptoms, addressing skin dryness, and mitigating depression in maintenance hemodialysis patients.